Associations of serum vitamin B12 and its biomarkers with musculoskeletal health in middle-aged and older adults - Zhao, Jiao; Lu, Qi; Zhang, Xianfeng (Frontiers in Endocrinology, 2024)
Introduction: The effects of vitamin B12 metabolism on musculoskeletal health and the exact mechanism have not been fully determined. Our study aimed to assess the association of vitamin B12 and its biomarkers with musculoskeletal health in middle-aged and older adults. Methods: The data from the National Health and Nutrition Examination Survey 2001-2002 were used to investigate the effects of serum vitamin B12 and its biomarkers (homocysteine and methylmalonic acid) on skeletal muscle health. Bone mineral density (BMD), lean mass, gait speed and knee extensor strength were used as indicators for musculoskeletal health. Results: Serum vitamin B12 level was positively correlated with the total and appendicular lean mass (β = 584.83, P = 0.044; β = 291.65, P = 0.043) in older adults over 65 years of age. In the full population, plasma homocysteine was associated with total lean mass, appendicular lean mass, gait speed, and knee extensor strength (all P < 0.05). Among older adults over 65 years of age, homocysteine level was significantly negatively correlated with gait speed and knee extensor strength (β = -12.75, P = 0.019; β = -0.06, P <0.001). Plasma methylmalonic acid was negatively associated with total BMD and femur BMD in the full population (β = -0.01, P = 0.018; β = -0.01, P = 0.004). In older adults, methylmalonic acid significantly affected total BMD, femur BMD and knee extensor strength (β = -0.01, P = 0.048; β = -0.01, P = 0.025; β = -7.53, P = 0.015). Conclusion: Vitamin B12 and its biomarkers are closely related to BMD, body composition, muscle strength and physical function in middle-aged and older adults. Vitamin B12 may be an important indicator of musculoskeletal health in the elderly.